Kerjasama Guru dan Orang Tua dalam Pembentukan Karakter Peserta Didik di Smp Negeri 15 Kota Bekasi - Jonni Iskandar; Hunafa Ulfitriyah; Zaimudin Zaimudin; Heny Narendrany Hidayati (Jurnal Syntax Admiration, 2024)
This study aims to analyze and describe the cooperation between teachers and parents in the formation of student character at SMP Negeri 15 Bekasi City. The focus of the research includes the form of cooperation, the character formation methods applied, as well as the supporting and inhibiting factors in the process. This study uses a qualitative approach with a case study method. Data was collected through observation, interviews, and documentation. The results of the study show that the cooperation between teachers and parents is formed through active communication, regular meetings, and parental involvement in various school activities. The character formation methods applied include religious habituation, discipline, and positive attitudes through school programs such as congregational dhuha prayers, tadarus Al-Qur'an, and social activities. The main supporting factors are high commitment from teachers and active support from parents, while the obstacles faced include time limitations and lack of awareness of some parents. In conclusion, harmonious cooperation between teachers and parents plays an important role in shaping the character of students who are religious, disciplined, and have noble character. It is recommended that schools strengthen communication and parent engagement programs to achieve optimal educational outcomes.